2011
DOI: 10.1371/journal.pone.0018062
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of a Novel Surveillance Paradigm for Complications of Mechanical Ventilation

Abstract: BackgroundVentilator-associated pneumonia (VAP) surveillance is time consuming, subjective, inaccurate, and inconsistently predicts outcomes. Shifting surveillance from pneumonia in particular to complications in general might circumvent the VAP definition's subjectivity and inaccuracy, facilitate electronic assessment, make interfacility comparisons more meaningful, and encourage broader prevention strategies. We therefore evaluated a novel surveillance paradigm for ventilator-associated complications (VAC) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(165 citation statements)
references
References 32 publications
(35 reference statements)
6
153
3
3
Order By: Relevance
“…At least 4 studies have evaluated consecutive subjects with VAEs to try to identify the clinical conditions that led to increases in ventilator support. 22,25,28,30 Findings from these studies are similar. The majority of VAEs are caused by pneumonia, fluid overload, atelectasis, and/or ARDS.…”
Section: Capacity To Guide Improvements In Care (Preventability)supporting
confidence: 60%
See 2 more Smart Citations
“…At least 4 studies have evaluated consecutive subjects with VAEs to try to identify the clinical conditions that led to increases in ventilator support. 22,25,28,30 Findings from these studies are similar. The majority of VAEs are caused by pneumonia, fluid overload, atelectasis, and/or ARDS.…”
Section: Capacity To Guide Improvements In Care (Preventability)supporting
confidence: 60%
“…They affect 5-10% of patients and have consistently been associated with longer duration of mechanical ventilation, longer hospital lengths of stay, more antibiotic usage, and higher mortality rates. [22][23][24][25][26][27][28][29][30][31][32] Multiple studies suggest that patients who develop VAEs are approximately twice as likely to die compared with similar patients who do not develop VAEs. [22][23][24][25][26][27][28][29][30][31][32] …”
Section: Clinical Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although pre-enrolment DMV exceeded 7 days [33] in just 12 (9.6%) patients (eight in the HFO-TGI group), the results of a recent multicentre trial imply that any difference in the overall management strategy of early ARDS might affect results for mortality [34].…”
Section: Limitationsmentioning
confidence: 99%
“…3,4 These events appear to be highly meaningful: studies from the United States, Canada, Australia, and Italy have consistently shown strong associations between VACs and prolonged length of stay in the ICU and between VACs and higher mortality rates. [3][4][5] These events are also potentially actionable: there is a great deal of existing literature on how to prevent and manage these four conditions. Subsequent tiers of ventilatorassociated events are designed to identify the subset of VACs that are infection-related and those that might indeed be pneumonias.…”
mentioning
confidence: 99%